Reading the papers: ideological cultures and media discourses on scientific knowledge - Carvalho, Anabela (2003)
Comunicação apresentada na Conferência “Does discourse matter? Discourse, power and institutions in the sustainability transition”, Hamburg, Germany, 11-13 July 2003.